Age-related differences in psychometric properties of World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) - Karsikas, Mika (My University, 2024)
The aim of this study was to detect a possible age-related differential item functioning (DIF) of the WHODAS 2.0 amongst people with musculoskeletal disorders. This was a cross-sectional study of 1,739 consecutive patients with chronic musculoskeletal pain at a university clinic. Difficulty and discrimination parameters were calculated for each of 12 items of the WHODAS 2.0 using item response theory. The presence of DIF was assessed both numerically and graphically. When considering differences in both difficulty and discrimination, a statistically significant DIF was observed for all the items except for the item “washing” (p-values <0.001). The DIF was mostly uniform. Items “standing”, “household responsibilities”, “learning a new task”, “emotional affectedness”, “concentrating”, “washing” and “dressing” showed better precision amongst older patients. Items “walking”, “dealing with strangers”, “maintaining a friendship” and “day-to-day work” were more informative amongst younger patients. The 12-item WHODAS 2.0 showed a significant age-related DIF in 11 out of 12 items among people with musculoskeletal pain. Difficulty and discrimination parameters were alike for all 12 items. The DIF was mostly uniform. Items “standing”, “household responsibilities”, “learning a new task”, “emotional affectedness”, “concentrating”, “washing” and “dressing” showed better precision amongst older patients. Items “walking”, “dealing with strangers”, “maintaining a friendship” and “day-to-day work” were more informative amongst younger patients. These results can be of use when applying the WHODAS 2.0 to people with musculoskeletal complaints, especially when the studied groups are predominated by people of certain age.
Keywords: tuki- ja liikuntaelinten sairaudet, poikkileikkaustutkimukset, psykometriikka, validointitutkimukset